THE VERBALIZATION OF THE CONCEPT OF PRESIDENT OF UKRAINE VOLODYMYR ZELENSKYJ IN THE GERMAN-LANGUAGE MEDIA - СЕМЕНЮК, Тетяна; БОНДАРЧУК, Олена; ПАСИК, Людмила (Current Issues of Foreign Philology, 2023)
The article examines the verbal representation of the concept PRÄSIDENT OF UKRAINE WOLODYMYR SELENSKYJ in the German-language media. In this paper, we distinguish between macroconcept and subconcept. The subconcept PRÄSIDENT DER UKRAINE WOLODYMYR SELENSKYJ is distinguished from the macroconcept PRÄSIDENT. All components of the concept that represent its various shades and features are those that belong to its nominative field, the structure of which has а nuclear, near-nuclear, and peripheral zones. The nuclear zone of the nominal field is the conceptual component of the concept that incorporates its definitional features (Staatsmann, Staatsoberhaupt, Vorsitzender, Politiker, Schauspieler, Regisseur, Komiker) and includes full synonyms of the concept, identified through contextual analysis of articles, websites and synonym dictionaries (Selenskyj, Präsident, Präsident der Ukraine, der ukrainische Präsident, der Ukraine-Präsident, Präsident Selenskyj, der ukrainische Präsident Wolodymyr Selenskyj). The core zone is characterised by the presence of incomplete synonyms, which include semantic, stylistic and contextual synonyms (Präsident im Krieg, Putins Gegenspieler, Putins Widersacher, Held, Verteidiger, medienbegabter Profi, talentierter Kommunikator, perfekter Frontmann, ehemaliger Komiker, ehemaliger Regisseur). The peripheral zone of the nominal field of the concept includes additional cognitive features that are evaluative and interpretative, i.e. accumulate additional layers on the language code, such as conceptual metaphors (Gesicht des Landes, Ikone des Wiederstands, Superman, Comic-Held, der biblische David). As a result of the analysis of the linguistic material, it was found that the lexical means used to verbalize the conceptual, figurative, and value components of the concept PRÄSIDENT DER UKRAINE WOLODYMYR SELENSKYJ belong, first of all, to the emotionally neutral vocabulary, which includes units typical for journalistic discourse.